Analisis Kesalahan Matematis Siswa Dengan Menggunakan Graded Response Models (GRM) Di SMP Negeri 5 Kupang - ole, marselina jeni bengo; Zulfikar, Ryan Nizar; Rukman, Nia Kurniaty (MEGA: Jurnal Pendidikan Matematika, 2023)
This qualitative descriptive study aims to determine the mathematical errors made by students using Graded Response Models on the triangle and square materials at class VII-C SMP Negeri 5 Kupang 2022/2023. The subject of this research is class VII-C SMP Negeri 5 Kupang, while the object is the students' mathematical errors using Graded Response Models (GRM). Data were analyzed based on the test results, interview results, and documentation and using Graded Response Models (GRM). The study shows that the mathematical errors of the students in class VII-C SMP Negeri 5 Kupang are in the high, medium, and low categories. High ability students consist of 4 students, medium ability students (7 students), and low ability students (4 students).